Bank competition and the price of credit: Evidence using Mexican loan-level data - Carlos Iván Ca\~nón; Edgar Cortés; Rodolfo Guerrero (Inter-American Development Bank (IDB), 2020)
This paper studies the relationship between competition measures at the bank level and the price of credit for non-financial firms in Mexico during 2009-2016. Two indicators of competition are constructed: the Lerner indicator and the Boone indicator. Evidence is provided that similar loans provided by banks with higher market power (Lerner indicator) are significantly more expensive: 11 percent higher than the mean interest rate. In addition, that price difference is concentrated in loans given out to microenterprises and small firms, and firms located in the central and southern regions of the country.
Keywords: G1; G21; L13; 330; Competition; Banks; Non -financial firms; Loan interest rate